Structuring of an educational health product on the concepts and formulas of the Content Validation Index (CVI): Experience report (Research, Society and Development, 2023)
Introduction: Education, due to the process of structuring and construction of knowledge by the student, has been evolving; a fact that led the apprentice to become, over the years, the protagonist of his own learning. This article aims to report the experience of the process of building an educational resource, on video, about the concepts and formulas of the IVC, using the CTM3 Method. Methodology: This article is an experience report that through to describe the process of building an educational resource, on video, about the concepts and formulas of the Content Validation Index (CVI), using the CTM3 Method. Results: The creation of the video was divided into two stages: 1st Stage - Pre-production, which structured the educational product using the CTM3 Method; and 2nd Stage - Production and Post-production, which recorded and edited the process. Conclusion: It was found that this experience report can help in the construction of an educational resource, on video, with the CTM3 Method, however, there is a need for future studies to validate it and confirm its scope and understanding by the interested public.